2019
DOI: 10.3389/fnana.2019.00047
|View full text |Cite
|
Sign up to set email alerts
|

Stereotaxic Coordinates and Morphological Characterization of a Unique Nucleus (CSF-Contacting Nucleus) in Rat

Abstract: A unique nucleus, the cerebrospinal fluid (CSF)-contacting nucleus, has recently been recognized in the brain parenchyma. The outstanding feature of this nucleus is that the neural somas are located in the parenchyma, but their processes stretch into the CSF, implying that it may be a key structure bridging the nervous and body fluids-regulating systems and may play a pivotal role in modulating physiological activities. However, the true biological significance of this nucleus needs to be uncovered. The morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 40 publications
2
41
0
Order By: Relevance
“…It is located within the ventral gray of the lower portion of the aqueduct (Aq) and upper portion of the fourth ventricle (4V) floor (Song et al, 2019). The outstanding feature of this nucleus is that the neural somata are located in the brain parenchyma but the processes stretch into the CSF (Song and Zhang, 2018;Song et al, 2019). The morphological connections of the CSF-contacting nucleus with non-CSF-contacting neurons, glia cells, and blood vessels have been confirmed with electron microscopy (Zhang et al, 2003).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…It is located within the ventral gray of the lower portion of the aqueduct (Aq) and upper portion of the fourth ventricle (4V) floor (Song et al, 2019). The outstanding feature of this nucleus is that the neural somata are located in the brain parenchyma but the processes stretch into the CSF (Song and Zhang, 2018;Song et al, 2019). The morphological connections of the CSF-contacting nucleus with non-CSF-contacting neurons, glia cells, and blood vessels have been confirmed with electron microscopy (Zhang et al, 2003).…”
Section: Introductionmentioning
confidence: 93%
“…), and heads were fixed on a stereotaxic instrument (Stoelting 51700, USA). A 1% CB solution (0.2 µl, Sigma, USA) was injected into the core of the CSF-contacting nucleus (Bregma: 8,242 ± 183 µm, Lateral: 92 ± 6 µm, Depth: 6,451 ± 109 µm; Song et al, 2019).…”
Section: Tracer Administrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on their functions, these nuclei can be divided In the past 30 years [3], our studies revealed that after injecting peripheral nerve tracer CB-HRP into the rat ventricular system, the tracer is confined to the ventricular wall because of the existence of the brain barriers. The CB positive neuron cluster is always present at the ventral grey of the lower part of the aqueduct and the upper part of the fourth ventricle floor [3][4][5][6]. Only the neural processes that stretch into the CSF can be labelled.…”
Section: Introductionmentioning
confidence: 99%